Generation Z Identification of the Concept of Authority and the Process of the Management of Media Messages in the Catholic Church - Zbigniew Widera; Wiktor Widera; Grzegorz Polok (Religions)
The growing importance of the influence of the media on the Catholic faithful calls for an answer to the question of to what extent the church’s activity in initiating messages of faith is subordinated to the logic and pragmatics of the media, which change the forms of the presence of religion in the lives of Catholics and the contexts in which it is positioned? As a result, it should force reflection: how to form and distribute religious messages using the tools of the media and, more generally, to manage the process of building relationships with the faithful. In this process, it is crucial to identify the factors influencing the faithful and especially the validity of existing values in their lives. The authors of this article focus on the concept of authority, identifying it in the research process conducted in Generation Z, aiming to form a conclusion as to whether it can constitute a value in the initiated media messages. The conducted study and its conclusions are considered from a Catholic perspective, referencing the importance of authority as one of the Church’s fundamental values. This value strengthens the building of a community of believers, as religious authorities, their behaviors, and views reinforce the transmitted ideas. The authority, which serves to enhance the conveyed messages, frequently appears in media transmissions. The concept of authority is explored in the theoretical section of the article.